DESCRIPTION OF EAT PATTERN AND RELATIONSHIP BETWEEN NUTRITION STATUS WITH BASIC CONSUMPTION LEVELS IN CHILDREN OF SCHOOL - Widiayunita, Miranti (Food Science and Technology Journal (Foodscitech), 2019)
Since the 2016 economic crisis, the number of poor people in Indonesia has increased. One of its impacts was the increasing number of street children. Street children are one of the conditions of children in a difficult situation and vulnerable livelihood, mainly on the aspect of health and their future. The aim of this research is to understand the nutritional status of street children as the scientific basis for further intervention programs. This research utilises the discrete-analytic observation by using quota sampling of 30 street children in the Tembokrejo Village. Nutritional status was assessed using the anthropometric parameters of height according to age and sex and carried out during 48 hours to determine their diet and consumption level. This research concluded that 70% of street children have poor nutritional status and only 6.7% have good nutritional status, most common diet patterns for street children are rice, side dishes and vegetables, level of consumption is still below the Nutritional Adequacy Rate (AKG) and no significant relationship between nutritional status and consumption level. This research suggests that intervention programs on street children need to be implemented to prevent further serious nutritional problems.